Harmonizing the Sharia Law on Islamic family matters in Malaysia: the issues and challenges / Nur Muhaimin Mohd Husaimi … [et al.] - Mohd Husaimi, Nur Muhaimin; Mohd Hanizam, Amaleena Syazwanie; Mohd Zaker, Nurul' Aliaa; Salehudin, Yasmin (2012)
This project paper discusses about the issues and challenges faced in order to harmonize the Shariah Law in Malaysia specifically in relating to the family matters. The project paper outlines our research proposal which consists of basic layouts in conduction our research. It also comprises of the introduction and history of Islamic Family Law before and after the establishment of Malaysia. Furthermore, this project paper explains about the administration of the Islamic Family Law in Malaysia and also the current issues involving the said matter. It nevertheless also highlights the establishments of the Shariah Judiciary Department in Malaysia and the challenges faced by the department. It also discussed about the Practice Note & Direction being issued by the Shariah Judiciary Department in Malaysia on the benefits and problems faced in implementing it. Besides, several parties to have depth knowledge in this topic had been interviewed to analyze on this matter which comprises of separate opinions and comments generated by legal expertise. Last but not least, the project paper focuses on the issue of non uniformity of the administration of the Shariah Judiciary Department in Malaysia together with the inconsistency of decision made by the Shariah Court judges as well as methods to prevent future occurrence regarding this problems.